The Students' Perception of English Teachers Competence at SMKN 1 Polewali - Fitriyani Barsyam Baharuddin; Abd. Haris Sunubi (Institut Agama Islam Negeri Parepare, 2021)
This study was aimed to see the students’ perception toward English teachers’ competence at SMKN 1 Polewali. The aim of this research is to get the empirical data about the Teachers’ competence by using Questionnaire. The population of this research comprises 270 students and the sample of the research is 65 students. So, from the students, the researcher had known about the English teachers’ competence. The research method used in this research was a qualitative and quantitative method or Mix-method by using a descriptive design. The data was collected through three instruments they are questionnaire, documentation and observation. So, the researcher used this method because it was a suitable method for this research to describe the students’ perception about the competencies of teachers. Based on the calculation, the result of the data analysis showed that the teachers’ competence got a mean score of 38.8 with percentage of 72.31% which was included average category. The teachers of SMKN 1 Polewali have a good competency but they still need to improve their competence.